The Effects of Service-Learning on College Students’ Attitudes Toward Older Adults - Augustin, Frankline (Gerontol Geriatr Educ, 2015)
The current U.S. healthcare workforce shortage is at crisis levels for providers who specialize in elder care (Harahan, 2011; Kovner, Mezey, & Harrington, 2002). Barriers such as ageism, lack of awareness of the need for workers, and lack of contact with seniors can impact the career choice of young professionals (Gross & Eshbaugh, 2011; Hutchison, Fox, Laas, Matharu, & Urzi, 2010; Lun, 2012). To explore ways to increase the number of students who pursue gerontology and to expand the elder care workforce, the researchers conducted a qualitative content analysis on the impact of service-learning in senior care facilities on students’ attitudes toward older adults. Students with senior contact reported increases in positive perceptions of seniors, discovered their own ageist stereotypes, and developed an interest in a career in elder care. Twenty-one months after the service-learning experience, students were surveyed again with their responses indicating continued positive attitude changes along with professional development demonstrating beneficial long-term effects from the experience.